EFFECT OF SELECTED DEMOGRAPHIC CHARACTERS ON HEALTH RELATED QUALITY OF LIFE (HRQOL) IN TYPE 2 DIABETIC SUBJECTS OF HYDERABAD AND RANGAREDDY DISTRICTS OF TELANGANA STATE - P. AMALA KUMARI, V. DAIVASHIROMANI, APARNA KUNA, S. SUCHARITHA DEVI and (The Journal of Research, PJTSAU, 2019)
The prevalence of diabetes is swiftly increasing over the globe at an alarming rate. According to the International Federation of Diabetes, 415 million adults around the world are suffering from diabetes, and it is estimated that the numbers will reach around 642 million by 2040 (IDF, 2015). The first World Health Organization (WHO) global report on diabetes demonstrates that the number of adults living with diabetes has almost quadrupled since 1980 to 422 million adults (WHO, 2016).